Laure M Sicard - GPU-accelerated 2D sediment transport model for hyper-turbid events in partially mixed estuaries (Jornada de Jóvenes Investigadores del I3A, 2025)
GPU-accelerated 2D sediment transport model for hyper-turbid events in partially mixed estuaries